Pengertian Al-Dilalah Al-Isyaariyah dan Al-Dilalah Al-Tasawwuriyyah; Serta Contoh Analisisnya dalam Teks Bahasa Arab - Fatmah Zaenal A.H,; Ummu Salamah,; Azzahra Emira S,; Wati Susiawati,; A. Dardiri, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This discussion outlines the theories of meaning in Arabic linguistics, focusing on Al-Dilalah Al-Isyaariyah (referential theory) and Al-Dilalah Al-Tasawwuriyyah (ideational theory). The referential theory, pioneered by Ogden and Richards, emphasizes the relationship between symbols (words), concepts, and referents (real objects), while the ideational theory, according to John Locke, positions meaning as an idea born of the human mind and conveyed through language. Both emphasize the role of words as a link between thought and reality, although the referential theory emphasizes concrete referents, while the ideational theory emphasizes mental concepts. Analysis of Quranic verses, Arabic poetry, and prose texts shows that meaning can be understood through two approaches: conceptualization (mental images in the mind) and referentiality (real referents in context). Thus, this discussion emphasizes the importance of understanding meaning as a process involving symbols, ideas, and reality for effective linguistic communication.